MENANAMKAN NILAI KEJUJURAN MELALUI PENDIDIKAN ANTI KORUPSI - Aeni Latifah; Septy Premitha; Sinta Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Anti-corruption education plays an important role in shaping students’ character and behavior, particularly in instilling the value of honesty. This study emphasizes three main aspects: the role of the curriculum and learning strategies, the role of teachers and the school environment, and the impact of anti-corruption education on students’ character. The integration of honesty values into the formal curriculum, through experiential-based approaches and reflective evaluation, has proven effective in enhancing understanding and internalization of moral values. Teachers and the school environment function as role models and moral laboratories, enabling students to connect theory with real-life practice. Anti-corruption education also has a long-term impact on character formation, preparing students to become individuals with integrity who are capable of facing ethical dilemmas. The findings of this study indicate that anti-corruption education is not merely a transfer of knowledge, but a sustainable moral investment for students and society.